Pengaruh Daya Organisasi Perilaku Kepemimpinan Pengambilan Keputusan dan Profesionalisme Kerja Terhadap Kinerja Karyawan pada Kantor Radio Republik Indonesia Kota Padang - Vira Afrianti (Strategic: Journal of Management Sciences, 2021)
This study aims to determine how much influence Organizational Culture, Leadership Behavior, Decision Making, and Professionalism Work on Employee Performance at the Radio Republik Indonesia Office, Padang City. The research variables are Organizational Culture (X1), Leadership Behavior (X2), Decision Making (X3), Work Professionalism (X4) and Employee Performance as variables (Y). Data Collection Methods Through Surveys and Distributing Questionnaires with a sample of 85 respondents. Given the importance of corporate culture, leadership behavior, decision making and work professionalism on employee performance at the Radio Republik Indonesia office, the author is interested in conducting research in the form of a thesis.